Physical capacity is associated with attention but not with general executive function in middle aged adults - Khalil Iktilat; Michal Isaacson; Roy Tzemah-Shahar; Maayan Agmon (PLoS ONE, 2025)
Associations between Physical Capacity (PC) and various aspects of executive function, including attention, have been identified in older and younger cohorts. Yet, the relationship among middle-aged individuals at the gateway of aging is largely understudied. The primary objective of this study was to investigate the relationship between physical capacity indicators and attention, a key component of executive functions, in middle-aged Muslims in Israel, a minority group experiencing chronic health disparities. This cross-sectional study included 255 participants (159 women, 96 men), aged 51.29 ± 4.26 (45–60 years). PC was assessed using the six-minute walk test (6MWT) and the 30-second sit-to-stand test (30 STS). Attention and executive function were assessed with the Stroop C Test and Trail Making Test (TMT) respectively. We found a statistical trend suggesting a positive correlation between the 30 STS and Stroop C scores, when controlling for age, sex, education level, and hemoglobin A1c, indicating that higher physical capacity is associated with better selective attention and response inhibition (β = 0.132, P = 0.057). In contrast, no correlation was found between the 30 STS and the TMT-B (β = −0.107, P = 0.107), suggesting that alternating attention and overall executive function are not associated with physical capacity in this cohort. Interestingly, neither functional assessment was associated with the 6MWT, suggesting that among healthy, free living, middle-aged individuals, a more challenging assessment, like the 30 STS may be most relevant when examining associations between physical capacity and executive function. Our findings highlight the nuances of the relationship between physical capacity and aspects of executive function in this demographic. These results add to the body of literature associating physical capacity to selective attention but not executive function in middle-aged, minority populations. Further extension of these findings can support healthy aging, ultimately enhancing quality of life and reducing morbidity in older age.